WORK SAFETY ASSURANCE SYSTEM OF WELDING WORKSHOP EMPLOYEES FROM ISLAMIC LAW AND LABOR LAW PERSPECTIVE: A CASE STUDY OF TANAH JAMBO AYE DISTRICT - Lilis Diatana; Edi Darmawijaya; Faisal Fauzan (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2018)
The employee safety is the responsibility of a company often ignored. The company is not optimal in doing safety effort for employees become one of its trigger. Welding garages in the sub-district of Tanah Jambo Aye is the company engaged in welding which has high level of potential hazard. In addition, the workers have to obtain the word safety that was listed in the law No. 13 year 2003 about employment. The problems will be discussed in this thesis are: (1) How is the employee safety guarantees system of welding garage in Tanah Jambo Aye sub-district? (2) How is the Islamic law perspective and the law No.13 year 2003 on the employee safety guarantees system of welding garage in Tanah Jambo Aye sub-district? . The first purpose of this research to know how is the employee safety guarantees system of welding garage in Tanah Jambo Aye. The last is to know how is the Islamic law perspective and the law No.13 year 2003 on the employee guarantees system of welding garage in Tanah Jambo Aye sub-district. The research methodology that is used in this research is descriptive analysis of Qualitative method. The result show the welding garage in Tanah Jambo Aye sub-district is less effective and not go well yet, because the welding garage company in that district do not provide perfect tool for personal protection in safety working, such as: hand protectors, masker, shoes, hat protections, and face protections. The risk happened in working or work accident can cause the employees disabled or injury, the all cases is not in full responsibility by the welding garage in Tanah Jambo Aye sub-district. This case less corresponding with Islamic concept, as intended in Maqashid Syari’ah by maintaining Al-umur al-dharuruyah that are maintaining the soul, religion, mind, descent, and treasure. Therefore, it can safety guarantee of the world and hereafter. Abstrak:Keselamatan pekerja Merupakan Tanggung jawab perusahaan yang sering diabaikan oleh perusahaan, salah satu penyebabnya adalah kurang optimalnya perusahaan dalam menyelenggarakan upaya keselamatan bagi karyawannya. Bengkel Las Kecamatan Tanah Jambo Aye merupakan perusahaan yang bergerak dibidang pengelasan yang memiliki tingkat potensi bahaya tinggi. Selain itu Keselamatan Kerja juga merupakan hak yang harus diperoleh pekerja yang sudah tercantum dalam Undang-undang No. 13 Tahun 2003 Tentang Ketenagakerjaan. Adapun Permasalahan yang di bahas dalam skripsi ini adalah: (1) Bagaimana Sistem Jaminan Keselamatan kerja Karyawan Bengkel Las Kecamatan Tanah Jambo Aye? (2) Bagaimana tinjauan Hukum Islam dan Undang-undang No.13 Tahun 2003 terhadap Sistem Jaminan Keselamatan kerja Karyawan Bengkel Las Kecamatan Tanah Aye? Tujuan Penelitian ini adalah Untuk mengetahui Bagaimana Sistem Jaminan keselamatan kerja Karyawan Bengkel Las Kecamatan Tanah Jambo Aye. Dan untuk mengetahui bagaimana tinjauan Hukum Islam dan Undang-undang No.13 Tahun 2003 terhadap Sistem Jaminan keselamatan Karyawan Bengkel Las Kecamatan Tanah Aye?. Metode yang digunakan dalam penelitian ini adalah metode Kualitatif yang berbentuk deskriptif analisis. Hasil Penelitian Menunjukkan bahwa Bengkel Las Kecamatan Tanah Jambo Aye dalam Melaksanakan Jaminan Keselamatan Kerja kurang Maksimal dan belum berjalan dengan baik karena Bengkel Las Kecamatan Tanah Jambo Aye belum sempurna dalam menyediakan alat-alat pelindung diri untuk keselamatan kerja Seperti: alat pelindung tangan, masker, sepatu, topi pelindung, alat pelindung wajah. Dan Bentuk Risiko yang terjadi dalam melakukan pekerjaan atau kecelakaan kerja yang dapat mengakibatkan para pekerja cacat ataau luka-luka, semua itu tidak di tanggung penuh oleh Bengkel Las Kecamatan Tanah Jambo Aye. Hal ini kurang sesuai dengan konsep Islam, sebagaimana yang dimaksud dalam Maqashid Syari’ah dengan memelihara Al-umur al-dharuriyah yaitu memelihara jiwa, agama, akal, keturunan dan harta sehingga dapat terjamin keselamatan dunia dan akhirat. Kata Kunci: Bengkel Las, Keselamatan Kerja, Hukum Islam, Hukum Ketenagakerjaan.